Mid-Parthian Pottery from Building V at Shahr-i Qumis. Issue 2 (3rd July 2019) - Stronach, Ruth; Stronach, David; Farahani, Alan; Parsons, Alison
ABSTRACT: This paper introduces the pottery of mid-Parthian date from Building V at Shahr-i Qumis, a major Parthian settlement that dates, at least in part, from the second and the first centuries BC, and which lies some thirty km to the west of Damghan. A little over two thousand years ago the local water supply appears to have been adequate to support a site that was notable for its monumental mud-brick architecture as well as for its pottery, which included a number of distinctive "Iron Age related" characteristics. This is not, however, a publication of the pottery from the entire site of Qumis; it represents pottery from the core plan of only one building, even if this particular building does much to illustrate the nature of typical mid-Parthian pottery in the vicinity of Qumis. Subsequent ceramic studies will complement the present treatment. Whether or not this same location ought also to be associated with a slightly earlier Achaemenid/Seleucid township that was known to the Greeks as Hecatompylos remains an unresolved issue.